Metabolic Evidence for the Involvement of a [delta]4-Palmitoyl-Acyl Carrier Protein Desaturase in Petroselinic Acid Synthesis in Coriander Endosperm and Transgenic Tobacco Cells. - Cahoon, E. B. (1994)
We have previously demonstrated that the double bond of petroselinic acid (18:1[delta]6cis) in coriander (Coriandrum sativum L.) seed results from the activity of a 36-kD desaturase that is structurally related to the [delta]9-stearoyl-acyl carrier protein (ACP) desaturase (E.B. Cahoon, J. Shanklin, J.B. Ohlrogge [1992] Proc Natl Acad Sci USA 89: 11184-11188). To further characterize the biosynthetic pathway of this unusual fatty acid, 14C-labeling experiments were conducted using developing endosperm of coriander. Studies were also performed using suspension cultures of transgenic tobacco (Nicotiana tabacum L.) that express the coriander 36-kD desaturase, and as a result produce petroselinic acid and [delta]4-hexadecenoic acid. When supplied exogenously to coriander endosperm slices, [1-14C]palmitic acid and stearic acid were incorporated into glycerolipids but were not converted to petroselinic acid. This suggested that petroselinic acid is not formed by the desaturation of a fatty acid bound to a glycerolipid or by reactions involving acyl-coenzyme As (CoA). Instead, evidence was most consistent with an acyl-ACP route of petroselinic acid synthesis. For example, the exogenous feeding of [1-14C]lauric acid and myristic acid to coriander endosperm slices resulted in the incorporation of the radiolabels into long-chain fatty acids, including primarily petroselinic acid, presumably through acyl-ACP-associated reactions. In addition, using an in vitro fatty acid biosynthetic system, homogenates of coriander endosperm incorporated [2-14C]malonyl-CoA into petroselinic acid, of which a portion was detected in a putative acyl-ACP fraction. Furthermore, analysis of transgenic tobacco suspension cultures expressing the coriander 36-kD desaturase revealed significant amounts of petroselinic acid and [delta]4-hexadecenoic acid in the acyl-ACP pool of these cells. Also presented is evidence derived from [U-14C]nonanoic acid labeling of coriander endosperm, which demonstrates that the coriander 36-kD desaturase positions double bonds relative to the carboxyl end of acyl-ACP substrates. The data obtained in these studies are rationalized in terms of a biosynthetic pathway of petroselinic acid involving the [delta]4 desaturation of palmitoyl-ACP by the 36-kD desaturase followed by two-carbon elongation of the resulting [delta]4-hexadecenoyl-ACP.